2018
DOI: 10.3389/fmicb.2018.00412
|View full text |Cite
|
Sign up to set email alerts
|

Macroalgae Extracts From Antarctica Have Antimicrobial and Anticancer Potential

Abstract: Background: Macroalgae are sources of bioactive compounds due to the large number of secondary metabolites they synthesize. The Antarctica region is characterized by extreme weather conditions and abundant aggregations of macroalgae. However, current knowledge on their biodiversity and their potential for bio-prospecting is still fledging. This study evaluates the antimicrobial and cytotoxic activity of different extracts of four macroalgae (Cystosphaera jacquinotii, Iridaea cordata, Himantothallus grandifoliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 28 publications
6
37
0
Order By: Relevance
“…Some studies on the effectiveness of extraction methods highlight that methanol extracts exhibit higher anticancer activity. 17,18 This result could be related to the presence of bioactive metabolites that are soluble in A. spicifera are possibly more effectively extracted in methanol solvent compared to ethanol. Treatment of A. spicifera methanolic extract was found significantly toxic in brine shrimps at 12 and 24 hr.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on the effectiveness of extraction methods highlight that methanol extracts exhibit higher anticancer activity. 17,18 This result could be related to the presence of bioactive metabolites that are soluble in A. spicifera are possibly more effectively extracted in methanol solvent compared to ethanol. Treatment of A. spicifera methanolic extract was found significantly toxic in brine shrimps at 12 and 24 hr.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs 2019, 17, x 2 of 36 halogenated compounds, sterols, terpenes, and small peptides, among other bioactive compounds [8][9][10][11]. Studies focusing on the preparation of macroalgae extracts and their chemical characterization revealed a large range of seaweed compounds with very interesting biological activities including antitumor, anti-inflammatory, antimicrobial, antidiabetic, antivirus, antihypertensive, fat-lowering, and neuroprotective activities [12][13][14][15].…”
Section: Phlorotanninsmentioning
confidence: 99%
“…Regarding clinical trials, studies with pure algal metabolites are scarce, limited to those carried out with kahalalide F and fucoxanthin. The majority of clinical trials currently aim to ascertain the effect of algae consumption, as extracts or fractions, on obesity and diabetes.Studies focusing on the preparation of macroalgae extracts and their chemical characterization revealed a large range of seaweed compounds with very interesting biological activities including antitumor, anti-inflammatory, antimicrobial, antidiabetic, antivirus, antihypertensive, fat-lowering, and neuroprotective activities [12][13][14][15].The large volume of studies proving the seaweed compound activities in in vitro systems [16][17][18][19] hints the need for further advancements in the knowledge about macroalgae compound efficiency in living systems (in vivo) and their use in the development of pharmaceuticals. In vitro studies are very relevant and yield very important information, but they only represent the first step of a long process, and the results obtained rarely reveal anything about the effects of a compound in vivo, because the responses observed in vitro can be magnified, diminished, or totally different in a more complex and integrated system.…”
mentioning
confidence: 99%
“…Identification of bioactive compound sources and screening for potential pharmacological activities are important aspects in order to develop novel tools for disease treatment (Santos et al 2015;Martins et al 2018). In this sense, macroalgae are reservoirs for possible bioactive compounds given their ability to biosynthesize secondary metabolites against environmental stress that include limited photoperiod, low temperatures and decreased nutrient availability (Santos et al 2017a;Passos et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research works showed that macroalgae can be sources of terpenes, phenols (Fernandes et al 2017), sterols, proteins (Pereira et al 2017), carbohydrates and lipids that are produced as secondary metabolites (Boulom et al 2014;Berneira et al 2020). The vast number of synthesized compounds can be associated with several biological activities reported in the literature including anti-inflammatory (Tenorio-Rodriguez et al 2017), antimutagenic (Osuna-Ruiz et al 2016), antiviral, antimicrobial (Martins et al 2018) and antioxidant actions (Alves et al 2016). Therefore, the characterization of chemical constituents from macroalgae can be an important tool in order to ascertain novel active substances and biological applications of these organisms (Martins et al 2018).…”
Section: Introductionmentioning
confidence: 99%